(untitled) (Journal of Comparative & International Higher Education, 2021)
In today’s information-driven society, the Japanese government envisions the next societal revolution as “Society 5.0,” where advanced technologies and service platforms integrate with and empower individuals in a human-based society. While Science, Technology, Engineering, and Mathematics (STEM) education has traditionally focused on technical skills and knowledge in isolation, this paper will look at the potential role and benefits of incorporating liberal arts education into these technical studies. This concept of integrating the liberal arts into STEM education is known as STEAM. The purpose of the study is to create a foundation for clarifying the role of interdisciplinary education in overcoming the vertical division of academic disciplines and restoring the “integrated nature” of scholarship. This study seeks to show how the humanities, social sciences, and arts can be used to enhance STEM education, and, furthermore, how this STEAM approach to education is key to enabling Japan’s vision for Society 5.0.